A Preloaded Amorphous Calcium Carbonate/Doxorubicin@Silica Nanoreactor for pH‐Responsive Delivery of an Anticancer Drug1. Issue 3 (24th November 2014) - Zhao, Yang; Luo, Zhong; Li, Menghuan; Qu, Qiuyu; Ma, Xing; Yu, Shu‐Hong; Zhao, Yanli
Abstract Biomedical applications of nontoxic amorphous calcium carbonate (ACC) nanoparticles have mainly been restricted because of their aqueous instability. To improve their stability in physiological environments while retaining their pH‐responsiveness, a novel nanoreactor of ACC–doxorubicin (DOX)@silica was developed for drug delivery for use in cancer therapy. As a result of its rationally engineered structure, this nanoreactor maintains a low drug leakage in physiological and lysosomal/endosomal environments, and responds specifically to pH 6.5 to release the drug. This unique ACC–DOX@silica nanoreactor releases DOX precisely in the weakly acidic microenvironment of cancer cells and results in efficient cell death, thus showing its great potential as a desirable chemotherapeutic nanosystem for cancer therapy.